Mortality Risk Stratification After Traumatic Brain Injury and Hazard of Death With Titrated Hypothermia in the Eurotherm3235Trial. Issue 5 (May 2017) - Andrews, Peter J. D.; Rodriguez, Aryelly; Suter, Peter; Battison, Claire G.; Rhodes, Jonathan K. J.; Puddu, Irene; Harris, Bridget A.
Abstract : Objectives: Hypothermia reduces intracranial hypertension in patients with traumatic brain injury but was associated with harm in the Eurotherm3235Trial. We stratified trial patients by International Mission for Prognosis and Analysis of Clinical Trials in [Traumatic Brain Injury] (IMPACT) extended model sum scores to determine where the balance of risks lay with the intervention. Design: The Eurotherm3235Trial was a randomized controlled trial, with standardized and blinded outcome assessment. Patients in the trial were split into risk tertiles by IMPACT extended model sum scores. A proportional hazard analysis for death between randomization and 6 months was performed by intervention and IMPACT extended model sum scores tertiles in both the intention-to-treat and the per-protocol populations of the Eurotherm3235Trial. Setting: Forty-seven neurologic critical care units in 18 countries. Patients: Adult traumatic brain injury patients admitted to intensive care who had suffered a primary, closed traumatic brain injury; increased intracranial pressure; an initial head injury less than 10 days earlier; a core temperature at least 36°C; and an abnormal brain CT. Intervention: Titrated Hypothermia in the range 32-35°C as the primary intervention to reduce raised intracranial pressure. Measurements and Main Results: Three hundred eighty-six patients were available for analysis in the intention-to-treat and 257 in the per-protocol population. The proportional hazard analysis (intention-to-treat and per-protocol populations) showed that the treatment effect behaves similarly across all risk stratums. However, there is a trend that indicates that patients in the low-risk group could be at greater risk of suffering harm due to hypothermia. Conclusions: Hypothermia as a first line measure to reduce intracranial pressure to less than 20 mm Hg is harmful in patients with a lower severity of injury and no clear benefit exists in patients with more severe injuries. Abstract : Supplemental Digital Content is available in the text.